THE EFFECT OF ADDING FLOUR WHITE OYSTER MUSHROOM (Pleurotus ostreatus) NUGGET IN FISH PROCESSING (Euthynnus affinis) ACCEPTANCE OF CONSUMER - Yuli, Herlima; Sari, N. Ira; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study was to determine the effect of oyster mushroom flour on the processing of tuna fish nuggets on consumer acceptance. The method used is an experimental method of conducting additional experiments flour oyster mushroom on the processing of tuna fish nuggets with 0, 5, 10, and 15 g concentrate. The parameters tested in the study is the organoleptic (taste, appearance, odor / aroma and texture) and the analysis (moisture, protein, fat, and fiber). Based on the tested parameter, tuna fish nuggets with the addition of white oyster mushroom flour 10g (N2) is the best treatment with the criteria in such a golden yellow color 3.66, distinctive flavor and a little tunny TJTP with the average value 3.46, soft and slightly crunchy texture 3.67 as well as a distinctive aroma wafted tuna with an average of 3.43 water content of 54.53, 16.84 protein content, fat content and levels of 1.49 fiber by 32.10.Keyword: nuggets, tuna, white oyster mushrooms